PRAGMATIC FUNCTION OF EMOJI AND STICKERS: ANALYSIS OF TELEGRAM CORRESPONDENCE - Rasuljonov Bexruzbek Ravshanjon o‘g‘li (TADQIQOTLAR, 2025)
ANNOTATION This article analyzes the pragmatic functions of emojis and stickers widely used in Telegram and other popular social media messengers. The study examines the role of emojis  and  stickers  in  expressing  a  person's  emotions  in  messages  written  through messengers and filling in communication elements that are difficult to express through written speech.  In addition, the pragmatic meanings of emojis, adaptable to various situations,  and  the  degree  of  their  influence  on  the  effectiveness  of  mutual communication, as well as the degree of their role in the development of relationships between people, are considered. According to the research results, the pragmatic features of visual symbols such as emojis and stickers in the era of modern digital technologies are highlighted.